Analisis Volatilitas Return Ethereum Menggunakan Model Threshold GARCH - 10060119001, Vizky Andharista Suhendar; Marizsa Herlina (Bandung Conference Series: Statistics, 2024)
Abstract. Volatility is a fluctuation or random change in return prices, in time series data volatility can cause heteroscedasticity or variance that is not constant where in general time series data must have a constant variance (homogeneous). Analysis that can be used in handling data with non-constant (heterogeneous) variance is using the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model. Return data is also identical to asymmetric changes in terms of negative and positive changes, it can also be analyzed with a special model, namely the Threshold GARCH model, where the TGARCH model considers positive and negative changes in return data to have different effects. The return data used in this study is Ethereum return data taken from the investment website and will be modeled using the TGARCH model. The first model estimated is the ARIMA (2,1,1) model. After testing the residual data, it was found that the ARIMA(2,1,1) model had an ARCH effect (heteroscedasticity), the second model estimated was the GARCH(1,1) model. After testing the residual data, it is found that the GARCH(1,1) model has an asymmetric effect, so the TGARCH model can be estimated. The best TGARCH model is the TGARCH(1,1) model. From the results of the research conducted, it can be concluded that the influence of positive allowances (good news) has a greater influence on the return value of ethereum than negative allowances (bad news). When there is a positive allowance, it will have an impact on the volatility of the Ethereum return value of 0.0006212. Meanwhile, when there is a negative allowance, it will have an impact on the volatility of the Ethereum return value of -0.32753. Abstrak. Volatilitas adalah fluktuasi atau perubahan harga return secara acak, dalam data time series volatilitas dapat menyebabkan terjadinya heteroskedastisitas atau varians yang tidak konstan dimana pada umumnya data time series harus memiliki varians yang konstans (homogen). Analisis yang dapat digunakan dalam menangani data dengan varians yang tidak konstans (heterogen) yaitu menggunakan model Generalized Autoregressive Conditional Heteroscedasticity (GARCH). Data return pun identik dengan perubahan asimetris dalam hal perubahan negatif dan positif, hal tersebut juga dapat dianalisis dengan model khusus yaitu model Threshold GARCH, dimana model TGARCH menganggap perubahan positif dan negatif pada data return memiliki efek yang berbeda. Data return yang digunakan dalam penelitian ini adalah data return Ethereum yang diambil dari website investasi dan akan dimodelkan menggunakan model TGARCH. Model pertama yang diestimasi adalah model ARIMA(2,1,1). Setelah dilakukan pengujian pada residual data, didapatkan hasil bahwa model ARIMA(2,1,1) memiliki efek ARCH (heteroskedastisitas), model kedua yang diestimasi adalah model GARCH(1,1). Setelah dilakukan pengujian pada residual data, didapatkan bahwa model GARCH(1,1) memiliki efek asimetris, maka model TGARCH dapat diestimasikan. Model TGARCH yang terbaik adalah model TGARCH(1,1). Dari hasil penelitian yang dilakukan dapat disimpulkan bahwa pengaruh gunjangan positif (good news) memiliki pengaruh yang lebih besar pada nilai return ethereum dibandingkan gunjangan negatif (bad news). Ketika terdapat gunjangan positif, maka akan berdampak pada volatilitas nilai return Ethereum sebesar 0.0006212. Sedangkan ketika terdapat gunjangan negatif, maka akan berdampak pada volatilitas nilai return Ethereum sebesar -0.32753.